Visualisasi Konsep Bangun Ruang Melalui Media Tri Matra dalam Pembelajaran Matematika di Sekolah Dasar - Syilla Fhadlilla Fharhah; Dena Aulia Yolanda; Nisrina Aura Andisa; Muhammad Nofan Zulfahmi (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
Mathematics is one of the main skills taught from elementary school to college, playing a role in developing critical and logical thinking patterns of students. However, many elementary school students have difficulty understanding mathematical concepts, especially spatial figures, due to the lack of supporting learning media. This study aims to explore the effectiveness of using Trimatra (three-dimensional) media in mathematics learning in elementary schools. Trimatra media, such as three-dimensional models of spatial figures, allows students to visualize and understand the characteristics and relationships between spatial figures in a concrete manner. The results of the literature study show that Trimatra media not only increases students' knowledge of mathematical concepts, but also motivates students to be actively involved in learning, increases critical thinking skills, and overall learning outcomes.